Cortical Aquaporin-4 in relation to brain oedema and neurological function of cortical cryo-injured mice. (October 2017) - Gandham, Edmond Jonathan; Vasudevan, Prabhakaran; Moorthy, Ranjith K.; Narasimhan, Kesavan; Murthy, Muthukumar; Rebekah, Grace; Rajshekhar, Vedantam
Highlights: 1.4-Fold increase in Aquaporin-4 (AQP-4) levels at 24 h following cerebral cortical cryoinjury in mice. This increase in AQP-4 expression was associated with worsening of neurological function. Decline in AQP-4 level at 48–72 h post injury and was associated with partial recovery of neurological function. Abstract: To estimate the spatial and temporal expression of Aquaporin-4 (AQP-4) in a murine model of automated cerebral cryoinjury and correlate AQP-4 expression with development of brain oedema and neurological function. AQP-4 levels were determined quantitatively by Western blots at site of injury and at sites adjacent to and distant from injury in brains of cryoinjured (experimental) ( n  = 18), sham injured ( n  = 18) & normal mice at 24, 48, 72 h post injury. AQP-4 expression was correlated with percentage water content of brain, Neurological Severity Score (NSS) and rotarod scores. We found a 1.4-fold increase in expression of AQP-4 at the site of injury and at sites distant from injury at 24 h when compared to normal mice ( p  = 0.05). The increase in expression of AQP-4 24 h post injury was significantly higher in experimental group at the site of injury and at the site adjacent to the injury in the ipsilateral hemisphere when compared to the sham injured mice ( p  = 0.05). At 24 h post injury the median NSS score in the experimental group was 9 (interquartile range 7.25–10) and that in the sham group was 0.5 (interquartile range 0.0–1.0) ( p  < 0.001). At 48 and 72 h, AQP-4 expression remained elevated in the experimental group when compared to normal brain, but the levels were not significantly different from that in sham group. AQP-4 expression was significantly elevated in the ipsilateral hemisphere in the first 24 h following cerebral cortical injury in mice and this could be correlated with worsening of neurological function. Over the next 48 h, there was a trend towards decrease in AQP-4 expression that was associated with partial recovery of neurological function.